dbANTHROP: Sistema de manejo de información antropométrica - Gamiño, S. M.; Cortés, E.; Caudillo, C. C. (Revista Mexicana de Ingenieria Biomedica, 2002)
Anthropometric studies are essential tools in human morphological and functional assessment. World most frequently used methods are based on measurement of skinfolds and circumferences. Body mass index (BMI), waist to hip ratio (WHR) and % body fat (%BF) are drawn from the recorded data. BMI, WHR and %BF are indicative of individuals health and functionality. Data collection, storage and analysis from large populations are highly time and effort consuming. Error probability increases due to complexity of calculation procedures required, and to operators fatigue. Both, representing limiting steps to use in simple paradoxes. The present work describes the construction and utilization of an anthropometric database for Spanish speaking users. We use a precomputed architecture, to establish 1 to 1 biyective relations. In addition, dbANTHROP automatically calculates body fat using the Jackson & Pollock, for 3 and 7 skinfolds, and Slaugther, for 2 skinfolds, equations. It estimates free fat, free fat mass and ideal weight, BMI and WHR. It is provided with powerful filtration and report tools, to select data for individuals or age, gender, race and anthropometric characteristics groups. The program works on Windows Microsoft®, under a friendly to user philosophy.